THE EFFECTIVENESS OF YOGA THERAPY ON DYSMENORRHOEA INTENSITY IN STUDENTS - Dhinny Novryanthi; Dede Nurhayati (Journal of Maternity Care and Reproductive Health, 2021)
This research is motivated by the incidence of dysmenorrhea in the range of 45-90% among women of productive age. The impact of dysmenorrhea on a mild or severe scale is very detrimental and disturbing on a mild or severe scale is very detrimental and disturbing for women who experience it, especially for young women who are still in school, it can interfere with their learning activities at school and often this causes decreased learning motivation. Handling of dysmenorrhea can be done with non-pharmacology, one of which is yoga. The research design was quasi experimental with 30 respondents divided into two groups of intervention and control. The results of this study were the effectiveness of yoga therapy on reducing pain intensity during dysmenorrhea in the intervention group. This can be concluded by the difference in the average pain scale score before and after the intervention. Obtained a significant value (Z = -3,434, p = 0.001 (p <0.005)). Whereas in the control group there was no significant change between those before and after the test was carried out because (Z = 0.000, p = 1,000 (p> 0.005)). The conclusion of this study is the effect of the effectiveness of yoga therapy on the intensity of dysmenorrhea in students of AKPER Cianjur.  The results of this study can be recommended for young women practicing yoga therapy while dysmenorrhea. For further researchers, it is expected to conduct qualitative research on respondent satisfaction responses to yoga dysmenorrhea.Keywords: Dysmenorrhea, menstruation, yoga.